2018
DOI: 10.1111/jcmm.13603
|View full text |Cite
|
Sign up to set email alerts
|

Up‐regulated deubiquitinase USP4 plays an oncogenic role in melanoma

Abstract: Melanoma is the most malignant skin cancer with increasing incidence worldwide. Although innovative therapies such as BRAF inhibitor and immune checkpoint inhibitor have gained remarkable advances, metastatic melanoma remains an incurable disease for its notorious aggressiveness. Therefore, further clarification of the underlying mechanism of melanoma pathogenesis is critical for the improvement of melanoma therapy. Ubiquitination is an important regulatory event for cancer hallmarks and melanoma development, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 38 publications
0
29
1
Order By: Relevance
“…Since its discovery, USP4 has been well characterized as a tumor promotor in multiple cancer types. For example, USP4 suppresses stress‐induced cell apoptosis and facilitates tumor metastasis in melanoma . USP4 promotes the suppressive function of Treg cells by interacting with and stabilizing interferon regulatory factor 8 (IRF8) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since its discovery, USP4 has been well characterized as a tumor promotor in multiple cancer types. For example, USP4 suppresses stress‐induced cell apoptosis and facilitates tumor metastasis in melanoma . USP4 promotes the suppressive function of Treg cells by interacting with and stabilizing interferon regulatory factor 8 (IRF8) .…”
Section: Discussionmentioning
confidence: 99%
“…See also Supporting Information Figure S4. [Color figure can be viewed at wileyonlinelibrary.com] facilitates tumor metastasis in melanoma. 26 USP4 promotes the suppressive function of Treg cells by interacting with and stabilizing interferon regulatory factor 8 (IRF8). 27 Furthermore, USP4 targets transforming growth factor-β-activated kinase 1 (TAK1) to regulate tumor necrosis factor-α (TNFα)-induced NF-κB activation.…”
Section: Discussionmentioning
confidence: 99%
“…In tissue samples from lung cancer patients, decreased expression of USP4 was associated with advanced cancer stage. In line with these results, a protective effect of USP4 was reported in lung adenocarcinoma and breast cancer patients, although distinct effects of USP4 have been reported for other cancer types [48][49][50][51][52][53]. For instance, expression of USP4 was downregulated in lung adenocarcinoma, and low USP4 expression was associated with poor overall survival and recurrence-free survival [48].…”
Section: Discussionmentioning
confidence: 54%
“…Moreover, expression of this DUB inhibited cell proliferation in vitro and suppressed tumor growth in an animal model [49]. In contrast, increased expression of USP4 was found in tissue samples from hepatocellular carcinoma, melanoma, esophageal cancer, and colorectal cancer, and USP4 was shown to be oncogenic in these cancer cells [50][51][52][53]. These results suggest that the expression and tumor promoting effect of USP4 may be cancer type specific and that aberrant expression of USP4 can either increase or decrease tumorigenesis depend on the different cell contexts.…”
Section: Discussionmentioning
confidence: 99%
“…USP4 is a deubiquitinating enzyme which may inhibit p53 by deubiquitinating an important p53 ubiquitin ligase ARF-BP1 [35]. Correspondingly, many studies have identified the oncogene effects of USP4 [36]. Here, on the contrary, we found that higher expressions of USP4 in LUAD may lead to better prognosis.…”
Section: Significant Somatic Mutations In Luadmentioning
confidence: 56%